THE EFFECT OF THE IMPLEMENTATION OF PROFESSIONAL ETHICS AND EMOTIONAL INTELLIGENCE ON DECISION MAKING FOR BPK RI AUDITORS OF RIAU ISLANDS PROVINCE - Harahap, Amas Augustian; Setijaningsih, Herlin Tundjung (International Journal of Application on Economics and Business, 2025)
This quantitative research examines how professional ethics and emotional intelligence affect BPK RI Representative of Riau Islands Province auditors' decision-making. Questionnaires provided first data. This research focuses on BPK RI Representative of Riau Islands Province auditors. The study used SPSS model 25 multiple linear regression. Professional ethics implementation, emotional intelligence, and decision making were examined as independent and dependent factors. The study reveals that professional ethics, evaluated by the BPK Code of Ethics' principles of independence, integrity, and professionalism, improve auditor decision-making. Auditor decision-making is affected by emotional intelligence, which includes self-awareness, self-control, motivation, empathy, and social skills.